2018
DOI: 10.1103/physrevmaterials.2.124601
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of twin-reduced III-V epitaxy on As-modified vicinal Si(111)

Abstract: Rotational twins are fundamental defects in III-V epitaxy, in particular for the growth on nonpolar (111) surfaces. Based on density functional theory (DFT) calculations, we develop a general model for III-V nucleation on vicinal non-polar (111)-oriented substrates and focus on the important differences in the atomic step configuration of different miscut directions. We verify this model by a relevant materials system when growing GaP epilayers on As-terminated Si(111): Scanning tunneling microscopy measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…This can be explained by the presence of an As 0 peak in Figure , suggesting the presence of excess As on the surface past the first monolayer. Scanning tunneling microscopy studies in ref showed a relatively high density of adatoms under certain As annealing conditions for (111) Si surfaces, which supports this explanation. The fit suggests that there is a fourth intermediate oxidation state of As present, as well.…”
Section: Resultsmentioning
confidence: 52%
“…This can be explained by the presence of an As 0 peak in Figure , suggesting the presence of excess As on the surface past the first monolayer. Scanning tunneling microscopy studies in ref showed a relatively high density of adatoms under certain As annealing conditions for (111) Si surfaces, which supports this explanation. The fit suggests that there is a fourth intermediate oxidation state of As present, as well.…”
Section: Resultsmentioning
confidence: 52%
“…The twin structures are summarized in Figure 1. Following convention for RTD formation on (111) surfaces, [38,39] the twinned and untwinned domains are referred to as α-Sb(111) and β-Sb(111), respectively. The registry between α-Sb(111) and the InAs substrate was Sb atoms on face-centred cubic (FCC)-like adsorption sites and β-Sb(111) on hexagonal close-packed (HCP)-like sites.…”
Section: Sample 1cmentioning
confidence: 99%